Pharmacokinetics and Pharmacodynamics of (S)-Ketoprofen Co-Administered with Caffeine: A Preclinical Study in Arthritic Rats - Raúl Medina-López; Nancy Vara-Gama; Olivia Soria-Arteche; Luis A. Moreno-Rocha; Francisco J. López-Muñoz (MDPI AG, 2018)
The purpose of the present study was to determine whether caffeine modifies the pharmacokinetics and pharmacodynamics of (S)-ketoprofen following oral administration in a gout-type pain model. 3.2 mg/kg of (S)-ketoprofen alone and combined with 17.8 mg/kg of caffeine were administered to Wistar rats and plasma levels were determined between 0.5 and 24.0 h. Additionally, antinociception was evaluated based on the protocol of the PIFIR (pain-induced functional impairment in the rat) model before blood sampling between 0.5 and 4.0 h. Significant differences in Cmax, AUC0-24, and AUC0-∞ values were observed with caffeine administration (p < 0.05). Also, significant differences in Emax, Tmax, and AUC0-4 values were determined when comparing the treatments with and without caffeine (p < 0.05). By relating the pharmacokinetic and pharmacodynamic data, a counter-clockwise hysteresis loop was observed regardless of the administration of caffeine. When the relationship between AUCe and AUCp was fitted to the sigmoidal Emax model, a satisfactory correlation was found (R2 > 0.99) as well as significant differences in Emax and EC50 values (p < 0.05). With caffeine, Emax and EC50 values changed by 489.5% and 695.4%, respectively. The combination studied represents a convenient alternative for the treatment of pain when considering the advantages offered by using drugs with different mechanisms of action.